Perempuan Disabilitas dan Hubungannya dengan Teologi Belas Kasih Katolik - Naibaho, Megawati; P Sipahutar, Antonius (Litbang STFT Widya Sasana Malang, 2024)
Abstract: Humans are the image of God and have the dignity of life as a special gift from God. In this regard, it must be noted that gender differences as men or women, normal physical conditions or as people with disabilities are never a measure of human dignity. Women with disabilities have the right to live and be loved like other human beings. Discrimination and various acts of injustice against women with disabilities are a moral issue that threatens the value of equal human dignity. This research aims to call for the need to realize Catholic theology of compassion, especially for women with disabilities. Women with disabilities are often ignored in various groups such as families, local communities, and in religious/religious circles. To overcome these problems and collect data and analyze problems comprehensively, this research uses case studies and qualitative methods through literature studies. Thus, the problem is studied through quantitative and qualitative approaches. First, I will explain that women with disabilities experience marginalization in general society; second, I will outline the idea of Catholic theology of mercy; Third, build a theological reflection and show the possible direction of pastoral theology. Through this research, the author hopes to be able to tell the concrete experiences of women with disabilities in relation to Catholic theology of compassion. In this way, it is hoped that there will be a joint movement that will increasingly promote peace, love, justice and prosperity. Keywords: human dignity; women with disabilities; mercy; discrimination